Trends in Tobacco Smoking in Pregnant Women: Data From French National Perinatal Surveys - Virginie Demiguel; Béatrice Blondel; Béatrice Blondel; Camille Bonnet; Camille Bonnet; Viêt Nguyen-Thanh; Marie-Josèphe; Marie-Josèphe; Nolwenn Regnault (Frontiers Media S.A., 2021)
Objectives: To describe maternal smoking trends in France between 1972 and 2016, and identify whether maternal characteristics associated with smoking in the 3rd trimester of pregnancy evolved between 2010 and 2016.Methods: Using French National Perinatal Surveys, we estimated proportions of smokers and the number of cigarettes smoked both just before pregnancy and during the 3rd trimester from 1972 to 2016. We used a Poisson model with robust variance to estimate prevalence ratios for smoking during pregnancy.Results: Proportions of mothers quitting smoking were relatively stable (46.0% in 1972 and 45.8% in 2016). The number of cigarettes smoked just before pregnancy and in the 3rd trimester decreased from 1995 onward. However, proportions of smokers remained high before (30.1%) and during the 3rd trimester in 2016 (16.2%). Smoking in the 3rd trimester was associated with a lower education level and lower income in both 2010 and 2016, whereas the association with age, country of birth and parity varied according to the survey year.Conclusion: Early targeted interventions are needed for smokers who plan to have a child and must take smokers' characteristics during pregnancy into account.